Key Approaches to Biblical Ethics : An Interdisciplinary Dialogue - Rabens, Volker,; Grey, Jacqueline,; Kovalishyn, Mariam Kamell, (Biblical Interpretation Series ;, 2021)
The purpose of Key Approaches to Biblical Ethics is to address fundamental as well as practical questions of methodology in examining the ethical material of the Bible. Sixteen scholars of international reputation, most of them leaders in the field of biblical ethics, discuss questions of biblical interpretation from the perspectives of the Hebrew Bible and New Testament ethics in close dialogue with one another. In the present volume both established and new approaches to biblical ethics are presented and discussed. The result is a volume of unprecedented scholarly interaction that provides key insights into issues of biblical ethics that play a significant role both for biblical interpretation as well as for methodological questions in Jewish and Christian ethics today.